The In-Between - Ansari, Rebecca K. S. (Walden Pond Press, 2022)
Cooper has felt adrift ever since his father left three years ago. Everything seems to get on his nerves including his annoying little sister Jess and the creepy girl next door. But when Cooper and Jess discover an unsolved mystery involving a railroad accident, Cooper becomes obsessed with solving it. The mystery involves a mysterious, unidentified dead boy whose only identifying feature is a strange insignia on his jacket. The siblings are shocked to realize that the strange girl next door has that same insignia on her jacket. They begin to investigate further and make a surprising discovery.